2020
DOI: 10.3390/molecules25092085
|View full text |Cite
|
Sign up to set email alerts
|

Computational NMR Spectroscopy of Ionic Liquids: [C4C1im]Cl/Water Mixtures

Abstract: In this work, I have analyzed the structure of binary mixtures of 1-butyl-3-methylimidazolium chloride ionic liquid, [C4C1im]Cl, and water, using computational NMR spectroscopy. The structure of the complex fluid phase, where the ionic and hydrophobic nature of ionic liquids is further complicated by the addition of water, is first generated by classical Molecular Dynamics (MD) and then validated by calculating the NMR properties with DFT at the ONIOM(B3LYP/cc-pVTZ//B3LYP/3-21G) on clusters extracted during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 45 publications
(58 reference statements)
3
22
0
Order By: Relevance
“…It can be concluded that the main 129 Xe chemical shift differences observed between the described ILs are due to the nature of the anion. The ILs can be grouped according to the type of anion and it is possible to observe five separate trends (dashed lines) between free volume and 129 distribution around Xe is more positive [110]. Accordingly, the increase in the alkyl chain of [Cnmim][NTF₂] and [Cnmim][PF₆], moves the 129 Xe chemical shift to the low field (deshielding).…”
Section: Experimental Techniques For Free Volume Determinationmentioning
confidence: 89%
See 4 more Smart Citations
“…It can be concluded that the main 129 Xe chemical shift differences observed between the described ILs are due to the nature of the anion. The ILs can be grouped according to the type of anion and it is possible to observe five separate trends (dashed lines) between free volume and 129 distribution around Xe is more positive [110]. Accordingly, the increase in the alkyl chain of [Cnmim][NTF₂] and [Cnmim][PF₆], moves the 129 Xe chemical shift to the low field (deshielding).…”
Section: Experimental Techniques For Free Volume Determinationmentioning
confidence: 89%
“…Another technique used to study the local structure of ILs was 129 Xe NMR spectroscopy. The Xenon atom can occupy cavities in liquids with enough space to accommodate it, [84,[107][108][109][110] and the chemical shift (δ) of free 129 Xe gas, which is close to 0 ppm, can increase up to several hundred ppm for strongly confined environments.…”
Section: Experimental Techniques For Free Volume Determinationmentioning
confidence: 99%
See 3 more Smart Citations